The concise Oxford dictionary of archaeology / Timothy Darvill - Darvill, Timothy
"This leading dictionary is the most wide ranging and comprehensive of its kind and covers all aspects of archaeology, including principles, techniques, artefacts, people, places, equipment, descriptive terms, and legislation. With over 4,000 fully revised and updated entries the Concise Oxford Dictionary of Archaeology remains the reference work for students, professionals, and enthusiasts."--book jacket.